Gene expression profiling for nitric oxide prodrug JS-K to kill HL-60 myeloid leukemia cells - Liu, Jie (2009)
The nitric oxide (NO) prodrug JS-K is shown to have anticancer activity. To profile the molecular events associated with anticancer effects of JS-K, HL-60 leukemia cells were treated with JS-K and subjected to microarray and real-time RT-PCR analysis. JS-K induced concentration- and time-dependent gene expression changes in HL-60 cells corresponding to the cytolethality effects. The apoptotic genes (caspases, Bax, and TNF-α) were induced, and differentiation-related genes (CD14, CD11b, and vimentin) were increased. For acute phase protein genes, some were increased (p53, c-jun) while others were suppressed (c-myc, cyclin E). The expression of anti-angiogenesis genes thrombospondin-1 and CD36 and genes involved in tumor cell migration such as tissue inhibitors of metalloproteinases, were also increased by JS-K. Confocal analysis confirmed key gene changes at the protein levels. Thus, multiple molecular events are associated with JS-K effects in killing HL-60, which could be molecular targets for this novel anticancer NO prodrug.